World Bank Support for Public Financial and Debt Management in IDA-Eligible Countries : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2021)
Sound public financial management and public debt management are critical to informing and implementing fiscal policy and to achieving the World Bank Group’s twin goals. When support for these two areas is complementary, public finance and debt management (PFDM) ensures that scarce public resources are used efficiently and for their intended purposes, including to finance growth-enabling spending and investment, and that debt burdens are sustainable and managed within acceptable cost and risk parameters. The importance of PFDM has increased significantly in International Development Association (IDA)-eligible countries in the face of rising debt vulnerabilities coupled with the heightened needs and reduced revenue associated with the COVID-19 pandemic. This evaluation provides an assessment of World Bank support to IDA-eligible countries for PFDM between FY08–17.